Optimizing Groundwater Aquifers Potential in The Development of Irrigation Wells for Agriculture Using Geo-Electrical Method - Rustadi Rustadi; O. T. Purwadi; I. G. B Darmawan (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
The identification of shallow groundwater aquifers is demanded to sustain the balance of utilization in agriculture and anticipate frictions that can occur due to the overlapping usage of groundwater resources. This study is aimed to identify the potential of groundwater resources based on the thickness and depth of the groundwater aquifer. Geoelectric resistivity methods have done with vertical electrical sounding (VES) and horizontal profiling techniques (2D mapping). The VES data acquisition was carried out with a Schlumberger array while 2D mapping by alpha Wenner array. Inversion results of vertical electrical sounding (VES) show that groundwater resistivity values in sedimentary rocks ranged from 1 to 100 ?m and in igneous rocks between 0.5 - 150 ?m. The results of 2D Resistivity Mapping also show that shallow aquifer depth ranged from 1 to 5 m with a thickness ranged from 15 m to more than 70 m. Meanwhile, bedrock depth ranged from 20 to 150 m with a pattern deeper to the west. Furthermore, the potential of groundwater aquifers in the development of irrigation wells for agriculture should be carried out in the western part of the study area. Keywords: Groundwater, Shallow Aquifer, Rock Resistivity, Irrigation Well, Geo-Electrical Sounding.